A New Iranian Phrynocephalus (Reptilia: Squamata: Agamidae) from the hottest place on earth and a key to the genus Phrynocephalus in southwestern Asia and Arabia - Kamali, Kamran; Anderson, Steven C. (Zootaxa, 2015)
A new species of agamid lizard, Phrynocephalus lutensis sp. nov., is described from the Lut Desert in Iran. It is a species adapted to wind-blown sand in this semi-isolated basin. It appears to be most closely similar to P. luteoguttatus and P. euptilopus on the basis of external morphology. A key to the 19 known Phrynocephalus species of southwestern Asia and Arabia is presented for the first time.